BEHAVIOUR OF ZIRCON IN HIGH-GRADE METAMORPHIC ROCKS: EVIDENCE FROM Hf ISOTOPES, TRACE ELEMENTS AND TEXTURAL STUDIES - Sláma J.; Košler J.; Pedersen R.B. (My University, 2007)
Hf isotopic data of minerals in a mafic pyroxene granulite from the southern Bohemian Massif, together with their major and trace element composition and petrological observations were used to decipher the metamorphic history and behaviour of zircon in the granulite. The Hf isotopic composition in the minerals was used to estimate whether the decompression reaction, namely the consumption of garnet and rutile, could have provided Zr for the formation of newly grown metamorphic zircon. The age of the decompression reaction indicated by the evolution of Hf isotopes in garnet and orthopyroxene is between 333 and 331 Ma, i.e. ca. 7 Ma younger than the available U–Pb zircon ages from the Moldanubian granulites and than the newly obtained 343 ± 2 Ma laser ablation ICP-MS U–Pb age of zircons. The combination of bulk and in-situ Hf isotopic data, major and trace element composition and petrological modeling of P–T evolution revealed that the formation of zircons can not be related to the decompression phase of the evolution of the mafic granulites.
Keywords: HF ISOTOPES; ZIRCON; GRANULITE; U-PB DATING; LASER ABLATION; ICP-MS; GARNET; DECOMPRESSION; METAMORPHIC REACTION